Direct and Residual Effect of Zn and Organic Manures on Yield, Zn Content and Uptake in a Rice (Oryza sativa) – Wheat (Triticum aestivum) Sequence on a Vertisol - R.S. Khamparia, P.S. Kulhare, G.D. Sharma, B.L. Sharma and (Journal of the Indian Society of Soil Science, 2014)
A field experiment was conducted at the research farm of Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur to study the effect of application of 4 levels of Zn (0, 1.25, 2.5 and 5.0 kg ha-1) and 4 sources of organic manures (FYM @ 10 t ha-1, poultry manure @ 5 t ha-1, pig manure @ 5 t ha-1 and without manure) in rice (JR201) and wheat (GW 273) in rice-wheat cropping sequence during 2007-08 and 2008-09 in a Vertisol. Zinc levels and organic manures were applied to rice crop during kharif 2007 and 2008 and their residual effect was studied in succeeding wheat crop. Application of 2.5 and 5.0 kg Zn ha-1 and its residual effect successively and significantly increased the grain yield, Zn content in grain and straw, Zn uptake by rice and wheat and DTPA extractable Zn after rice and wheat, respectively. The application of FYM, poultry manure and pig manure and their residual effect significantly increased the yield, Zn content in and uptake by rice and wheat, respectively over control, except Zn content in rice grain with FYM and pig manure. However, application of poultry manure was found significantly superior to FYM and pig manure in respect of Zn uptake by rice, wheat yield, Zn uptake by wheat and DTPA extractable Zn. Application of poultry manure along with 1.25 kg Zn ha-1 gave the maximum yield of wheat.